A novel injectable platelet-rich fibrin reinforced papilla reconstruction technique - Komal Puri; Manish Khatri; Mansi Bansal; Ashish Kumar; Mohd Rehan; Aneesha Gupta (Wolters Kluwer Medknow Publications, 2022)
Formation of black triangles due to the loss of interdental papilla is one of the utmost perplexing esthetic problems of the periodontium. Many surgical and nonsurgical treatment options have been researched upon to obtain complete papillary fill, but minimally invasive procedures have always been the choice of treatment both for the operator as well as the patient. This article describes the use of injectable platelet-rich fibrin (i-PRF) as a novel nonsurgical technique for the reconstruction of deficient interdental papilla. This is probably the first article that describes the use of i-PRF for the nonsurgical treatment of black triangles. Six sites with the presence of deficient interdental papilla in four patients were selected for this case series. After completion and reevaluation of scaling and root planing, autologous i-PRF was injected at the base of the interdental papilla using the insulin syringe. Photographs obtained before the treatment and at 1, 3, and 6 months after the intervention were assessed by Image J software along with clinical measurements. The use of novel nonsurgical injectable PRF technique allows clinician to successfully treat deficient interdental papilla.